Melhoria da produtividade por meio da aplicação de gestão por processos em um frigorifico de suínos - Benin, Denian Antonio (2024)
The search for optimizing production in small companies comes up against need to maintain or increase the quality of products offered without increasing excessive costs. The challenge increases even more when it comes to companies in expansion. In this context, process management is a strategy already used by large companies, however the method used in this study focuses on a company considered medium size. The present work aims to map the current production process, apply a process management method, plan measures that result in increased production capacity, in a pig slaughterhouse located in the north of Rio Grande do Sul. Proposing the optimization of process productivity through the use of a viable action for the company, whose main focus is increasing slaughter efficiency, elimination of waste, product quality, safety and ergonomics.